Osteogenic signaling on silk-based matrices. (August 2016) - Midha, Swati; Murab, Sumit; Ghosh, Sourabh
Abstract: Bone tissue engineering has mainly focused on generating 3D grafts to repair bone defects. However, the underlying signaling mechanisms responsible for development of such 3D bone equivalents have largely been ignored. Here we describe the crucial aspects of embryonic osteogenesis and bone development including cell sources and general signaling cascades that guide mesenchymal progenitors towards osteogenic lineage. Drawing from the knowledge of developmental biology, we then review how silk biomaterial can regulate osteogenic signaling by focusing on the expression of cell surface markers, functional genomic information (mRNA) of stem cells cultured on silk matrices. In an attempt to recapitulate exact in vivo microenvironment of osteogenesis, role of scaffold architecture and material chemistry in regulating cellular differentiation is elaborated. The generated knowledge will not only improve our understanding of cell-material interactions but reveal newer strategies beyond a conventional tissue engineering paradigm and open new prospects for developing silk-based therapies against clinically relevant bone disorders. Graphical abstract: Knowledge on the mechanism of bone development and the corresponding signaling cascades is vital for the development of functional 3D bone graft models. This review focuses on the osteogenic potential of silk-based matrices and the underlying signaling mechanisms that regulate osteogenesis as a function of the physical (scaffold topography and pore architecture), chemical (decorated chemical groups) and biological (cell sources and immobilized/soluble growth factors) factors.